Sistematika Literatur : Faktor – Faktor Kesepian pada Usia Remaja - Wahyu Eka Febriliyani; Ni’matuzahroh (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Loneliness is a problem that is often experienced by adolescents. Many factors can influence the occurrence of loneliness in adolescents. This systematic literature review aims to explore what factors influence adolescent loneliness. Journal searches were conducted using Scopus and Google Scholar databases with the keywords “loneliness in adolescents and young adulthood”. A total of 6 studies that fit the inclusion and exclusion criteria were then analyzed to identify the factors that cause loneliness in adolescents. These factors included gender, friendship quality, social media use, social relationships with peers, self-esteem and social acceptance. The results of this study are expected to provide a deeper understanding of the factors that cause loneliness in adolescents so that its negative impact can be anticipated and prevented.